Sequential Regulation of the Small GTPase Rap1 in Human Platelets - Franke, Barbara (American Society for Microbiology, 2000)
Rap1, a small GTPase of the Ras family, is ubiquitously expressed and particularly abundant in platelets. Previously we have shown that Rap1 is rapidly activated after stimulation of human platelets with α-thrombin. For this activation, a phospholipase C-mediated increase in intracellular calcium is necessary and sufficient. Here we show that thrombin induces a second phase of Rap1 activation, which is mediated by protein kinase C (PKC). Indeed, the PKC activator phorbol 12-myristate 13-acetate induced Rap1 activation, whereas the PKC-inhibitor bisindolylmaleimide inhibited the second, but not the first, phase of Rap1 activation. Activation of the integrin α(IIb)β(3), a downstream target of PKC, with monoclonal antibody LIBS-6 also induced Rap1 activation. However, studies with α(IIb)β(3)-deficient platelets from patients with Glanzmann's thrombasthenia type 1 show that α(IIb)β(3) is not essential for Rap1 activation. Interestingly, induction of platelet aggregation by thrombin resulted in the inhibition of Rap1 activation. This downregulation correlated with the translocation of Rap1 to the Triton X-100-insoluble, cytoskeletal fraction. We conclude that in platelets, α-thrombin induces Rap1 activation first by a calcium-mediated pathway independently of PKC and then by a second activation phase mediated by PKC and, in part, integrin α(IIb)β(3). Inactivation of Rap1 is mediated by an aggregation-dependent process that correlates with the translocation of Rap1 to the cytoskeletal fraction.